Salsolaius gen. nov. a new genus of Apalochrini (Coleoptera, Melyridae, Malachiinae) from the salt Lake Way of Western Australia - Liu, Zhenhua; Ślipiński, Adam; Pang, Hong (Zootaxa, 2021)
Apalochrini comprises nearly half of the genera of Australian Melyridae, which are all recognized by male specific characters, and are commonly found on grasses, flowers and riverside or seashore rocks. Here we describe a new genus Salsolaius gen. nov. from Lake Way of Western Australia, representing the first known genus of Australian Melyridae inhabitating in salt lakes. The new genus can be easily distinguished by asymmetrically biserrate antennae and exposed apical abdomen from above in both male and female, the former characters is firstly found in Melyridae. Consequently, Salsolaius biserratus sp. nov. was described as the type species of this genus. An updated key to genera of Australian Apalochrini is provided.